51st AIAA/SAE/ASEE Joint Propulsion Conference 2015
DOI: 10.2514/6.2015-4083
|View full text |Cite
|
Sign up to set email alerts
|

Direct Thrust Measurements of an EMDrive and Evaluation of Possible Side-Effects

Abstract: The EMDrive has been proposed as a revolutionary propellantless thruster using a resonating microwave cavity. It is claimed to work on the difference in radiation pressure due to the geometry of its tapered resonance cavity. We attempted to replicate an EM Drive and tested it on both a knife-edge balance as well as on a torsion balance inside a vacuum chamber. After developing a numerical model to properly design our cavity for high efficiencies in close cooperation with the EM Drive's inventor, we built a bre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
19
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 8 publications
2
19
0
Order By: Relevance
“…T WAS previously reported that radio-frequency (RF) resonant cavities generated anomalous thrust on a low-thrust torsion pendulum [1,2] in spite of the apparent lack of a propellant or other medium with which to exchange momentum. It is shown here that a dielectrically loaded, tapered RF test article excited in the transverse magnetic 212 (TM212) mode (see Fig.…”
mentioning
confidence: 99%
“…T WAS previously reported that radio-frequency (RF) resonant cavities generated anomalous thrust on a low-thrust torsion pendulum [1,2] in spite of the apparent lack of a propellant or other medium with which to exchange momentum. It is shown here that a dielectrically loaded, tapered RF test article excited in the transverse magnetic 212 (TM212) mode (see Fig.…”
mentioning
confidence: 99%
“…This level of force seems high enough to be measurable with a commercial precision balance which has short response time as opposed to that of the torsion pendulum [1,2]. This type of measuring instrument has already been used to detect an EMDrive force [3,7], and it allows us to develop an accurate-enough, handy, and low-cost measuring setup.…”
Section: Solutionsmentioning
confidence: 99%
“…This contentious atmosphere prompted other research teams around the world to publish their own studies on this topic, both on an experimental level [1][2][3] and on a theoretical one [4,5]. In 2016, in the first one of the few peer-reviewed papers, White et al, from Eagleworks Laboratories (NASA Johnson Space Center), stated that their cavity type, named QVPT (quantum vacuum plasma thruster), produced a force with a thrust to power ratio of 1.2 ± 0.1 mN/kW [1].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Possible side-effects have been pointed out, and hence certain experiments have been inconclusive about the thrust. 10 Also credibility of some earlier experimental results has been recently reconsidered in relation to instrumental precision. 11 Since explanations 12,13 and their refutations [14][15][16][17] have not been conclusive, we bring up a new line of thought to the profound discourse that targets to important applications, most notably to keep satellites on orbits.…”
Section: Introductionmentioning
confidence: 99%